PEMBERDAYAAN PETANI JAGUNG MELALUI PENGEMBANGAN USAHA DIVERSIFIKASI PRODUK OLAHAN JAGUNG DI LABUAPI KABUPATEN LOMBOK BARAT - Citra Ayu Dewi; Yeti Kurniasih (Lumbung Inovasi: Jurnal Pengabdian kepada Masyarakat, 2017)
In general the problem and the main obstacle in the Corn Growers Labuapi area is the lack of effort and a good development in the processed product diversification efforts highly selling corn and economic value. This condition is due Labuapi local farming communities are not familiar with the processing technology. Moreover, public interest in the corn-based food is still low. This is caused by lack of knowledge of some people about the nutritional value of corn, corn display food products less attractive, and the assumption that maize is only consumed by the economically weak. KKN PPM activities that have been carried out aims to increase the diversity of corn refined products through the application of technology diversified development of corn processing products are cheap and easily applied by farmers maize. KKN-PPM have been conducted for 3 months in the second semester of the academic year 2016. The activities that have been undertaken include: increased KKN-PPM on the student, training and assistance directly to the corn farmers in the form of diversified products such as milk processed maize corn, noodles corn, corn and soybean corn dodol. Based on the results of the training has been done obtained a level of understanding and skills of the communities (farmers corn) in the village of telagawaru satisfactory, while the quality of the corn processed products produced successful or maximum.